Synthesis, spectral and surface investigation of novel CaMgB2O5:Dy3+ nanophosphor for UV based white LEDs. (July 2017) - Kumar, Vinay; Manhas, M.; Bedyal, A.K.; Swart, H.C.
Graphical abstract: Highlights: Synthesis, spectral and surface investigation of novel CaMgB2 O5 : Dy 3+ nanophosphor for UV based white LEDs. XPS studies confirm the presence of all the possible elements in CaMgB2 O5 :Dy 3+ . Upon 349 nm excitation, this phosphor shows peaks at 484 nm (blue), 576 nm (yellow) and 662 nm (red). Abstract: This paper reports the surface, spectral and luminescent properties of Dy 3+ doped CaMgB2 O5 phosphor synthesized by combustion method. X-ray diffraction (XRD) was used to characterize the phase structure. X-ray photoelectron spectroscopy (XPS) was used to investigate the surface elemental composition and chemical states of the synthesized phosphor. The luminescent properties of CaMgB2 O5 :Dy 3+ phosphor was investigated by using photoluminescence emission, excitation and reflectance spectra. The excitation spectra under 576 nm emission consist of charge transfer band (CTB) and a series of 4f-4f transition states of Dy 3+ ion. The emission spectra of CaMgB2 O5 :Dy 3+ phosphor recorded at 349 nm excitation shows sharp peaks at 485 nm, 576 nm and 665 nm assigned to 4 F 9/2 → 6 H J/2 ( J = 15, 13, and 11) transitions of Dy 3+ ion. The CIE chromaticity color coordinates (0.38, 0.40) of CaMgB2 O5 : Dy 3+ phosphor falls in the yellowish white region of the horse shoe plot of color gamut. The band gap of the material was calculated to be 5 eV. The phosphor decay curve was also determined. The results show that CaMgB2 O5 :Dy 3+ phosphor might be potential phosphors for n-UV-based white light-emitting diodes.